ANALISIS KEWAJIBAN KEPESERTAAN SISTEM BPJS KESEHATAN - Shella Virgina Umma Al Asyari; Budiarsih Budiarsih (Gapenas Publisher, 2022)
The National Health Insurance is a government policy in the health sector that aims to realize the provision of proper health insurance for all people. In Indonesia, BPJS is the only institution designated to carry out the goals of JKN, so that people are required to become BPJS participants through regulations mandated by the government but in the implementation of these obligations there are many challenges or problems. On this basis, this research focuses on. How is the problem of BPJS Health membership obligations from the perspective of justice. The method used is the method of analysis, this type is normative legal research conducted to examine secondary legal materials, also using the approach method, namely the statute approach and the conceptual approach, which will provide recommendations as input material for revising laws or the health system. The results of the study found that among the poor who could not register themselves as BPJS Kesehatan members, health insurance from the state for the community was still found to be inequitable. Administrative problems and health services provided, the existence of a management system that is not linear with the needs of the community has the potential to cause injustice that is accepted by the community